Evaluasi Tax Control Framework Perusahaan Dagang dalam Menghadapi UU HPP - Narwastu Angela Nababan (Jurnal Riset Akuntansi & Perpajakan (JRAP), 2023)
Clear and structured tax regulations are very important in a country's economic system, but they can change along with developments over time and economic policies. This change can be caused by the increasing complexity of tax regulations, which can trigger non-compliance and tax avoidance that is detrimental to the country. This research aims to evaluate the readiness of trading companies, especially PT. H, in facing the harmonization of tax regulations and to determine the impact. PT. H as a trading company was chosen because trading companies have a simpler financial structure compared to manufacturing companies and service companies. This makes it a good case study for understanding the impact of tax law changes without too many other complex factors involved. This research uses the Tax Control Framework indicators from the OECD, which include tax strategy, control, division of tasks, documentation of the tax implementation process, and monitoring of tax implementation. The evaluation results show that PT. H has taken strategic steps such as monitoring regulations, partnering with tax consultants, and implementing strict controls to ensure the accuracy of tax reporting. They also carry out focused division of tasks, detailed documentation, and regular internal monitoring and audits. Despite facing several challenges such as understanding complex regulations and lack of government outreach, PT. H remains committed to maintaining tax compliance and optimal company performance.